Impact Of Work Experience, Interpersonal Relationship And Employee’s Capability On Work Stress Of Industrial Bank’s Employees In Zhengzhou, China - Xu, Yu-Xie; Syarifah Mastura, Syed Abu Bakar (INTI International University, 2019)
Abstract should be concise, and should include Problem statement, objectives, methodology, results and discussion, and summary for research paper. The novelty or new findings of the research should be highlighted as well Increase in digitalization has transformed the banking industry. The advantage of the location in which companies have a competitive advantage is disappearing, as companies have started operating globally. This phenomenon of expansion, which is also referred to globalization, has empowered the customers but overstressed the employees in all sectors of life. The banking industry is no exception. Due to increased competition, the work stress of employees in the bank sector in China is rising. It has been proved through many studies that, the work stress is caused by excessive workload, which ultimately impacts both mental and physical health of employees. Impact on psychological and physical health ultimately effect job satisfaction and employee work performance. Therefore this paper has studied the work stress of Industrial Banking employees in Zhengzhou Branch of Industrial Bank. The study, core hypothesis is that work stress can be reduced by work experience , interpersonal relationships, and enhancing employees’ capability. The responses were collected using a questionnaire. The study is a quantitative and cross sectional study. Total 320 respondents responses were collected and analyzed using SPSS. Through using multiple regression analysis, the researcher found that the study hypotheses are valid for Zhengzhou Industrial Banking employees. The study concluded that interpersonal relationship, work experience and employee capability has a significant positive impact on work stress of industrial bank’s employees in Zhengzhou, CHINA The study concluded that if the employees get the experience and training; their interpersonal skills are better, and if they are capable of doing their job’ then they can also handle the work stress. The human resources managers are recommended to train employees to improve the interpersonal skills of employees for better job performance and reduction in stress. Future researchers are recommended to study the stress impact on the demographic level.